Controlled Release of Ibuprofen by Using Morphologically Modified Mesoporous Silica - Sana Ahmad; Javariah Javaid; Wajeeha Fatima (Advances in Materials Science and Engineering)
The synthesis of mesoporous silica with variable pore sizes was carried out for the purpose of controlled drug release study. Mesoporous silica containing three-dimensional cagelike structures was prepared by the simple hydrothermal method using triblock copolymer Pluronic F-127 as the template and tetraethyl orthosilicate (TEOS) as a silica source. The synthesized samples of plain and modified mesoporous silica were compared to measure the drug release ability of ibuprofen. The effect of cosurfactants, temperature, and different salts on the pore structure of the materials were also observed. The surface property enhancement of mesoporous silica was contributed by controlling its pore morphology. The materials were characterized by FT-IR, SEM, TGA, and UV-Visible spectroscopy and later used for the ibuprofen release study. The results indicated that the modified mesoporous silica with increased pore diameter showed increased storage capacity and high pH-responsive release behavior as compared to the plain mesoporous silica.